1994
DOI: 10.1002/eji.1830240111
|View full text |Cite
|
Sign up to set email alerts
|

On the biological origin of anti‐double‐stranded (ds)DNA antibodies: systemic lupus erythematosus‐related anti‐dsDNA antibodies are induced by polyomavirus BK in lupus‐prone (NZBxNZW) F1 hybrids, but not in normal mice

Abstract: We have recently demonstrated that polyomavirus BK and isolated BK double-stranded (ds)DNA have a strong potential for induction of anti-dsDNA antibodies. Here, data are presented that demonstrate that normal mice (a term used in this report for mice not predisposed to a lupus-like syndrome) of four different strains responded to both BK virus and BK dsDNA by producing transient antibodies binding preferentially to the viral dsDNA itself. These antibodies did not bind in the Crithidia luciliae assay, and did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 13 publications
3
27
2
3
Order By: Relevance
“…The titers of the Abs determined in solid-phase (conventional anti-dsDNA ELISA) and in solution-phase anti-DNA ELISA (SPADE) using linear and circular dsDNA molecules, compared well with those currently determined in autoimmune (NZBϫW)F 1 mice (manuscript in preparation), and with those determined by the same solid-and solution-phase assays recently published for human SLE-derived anti-dsDNA Abs (27), which differ significantly from the much higher titers reported for Abs to nonself proteins or to Z DNA, as discussed by Stollar (43). The results of these experiments directly demonstrated that T-Ag expression initiated a process that resulted in continuous stimulation of autoimmune dsDNA-specific B cells, most probably due to release of heterologous nucleosome-T-Ag complexes able to initiate cognate interaction between DNA-specific B cells and T-Ag-specific T cells (13)(14)(15)(16)(17)44). The exact process involved in release of nucleosome-T-Ag complexes after expression of T-Ag is not fully determined, but may be caused by cytotoxic CD8 ϩ T cells activated in context of T-Ag expression.…”
Section: Analyses Of T Cell Responses (Mean Cpm ϯ Sd) To Nucleosomementioning
confidence: 90%
“…The titers of the Abs determined in solid-phase (conventional anti-dsDNA ELISA) and in solution-phase anti-DNA ELISA (SPADE) using linear and circular dsDNA molecules, compared well with those currently determined in autoimmune (NZBϫW)F 1 mice (manuscript in preparation), and with those determined by the same solid-and solution-phase assays recently published for human SLE-derived anti-dsDNA Abs (27), which differ significantly from the much higher titers reported for Abs to nonself proteins or to Z DNA, as discussed by Stollar (43). The results of these experiments directly demonstrated that T-Ag expression initiated a process that resulted in continuous stimulation of autoimmune dsDNA-specific B cells, most probably due to release of heterologous nucleosome-T-Ag complexes able to initiate cognate interaction between DNA-specific B cells and T-Ag-specific T cells (13)(14)(15)(16)(17)44). The exact process involved in release of nucleosome-T-Ag complexes after expression of T-Ag is not fully determined, but may be caused by cytotoxic CD8 ϩ T cells activated in context of T-Ag expression.…”
Section: Analyses Of T Cell Responses (Mean Cpm ϯ Sd) To Nucleosomementioning
confidence: 90%
“…Even methylated BSA carrier-specific T cells could help in the production of anti-DNA autoantibodies when B/W lupus mice were immunized with methylated BSA-DNA complex (65). However, herein we have determined which of the naturally occurring and abundant autoantigens could trigger the spontaneously arising Th cells of lupus that preferentially induce potentially pathogenic anti-DNA autoantibodies.…”
Section: Introductionmentioning
confidence: 88%
“…Deliberate immunization of mice with various DNA-binding proteins of exogenous or endogenous origin along with CFA leads to the production of anti-DNA autoantibodies, particularly in lupus-prone genetic backgrounds (63)(64)(65). Even methylated BSA carrier-specific T cells could help in the production of anti-DNA autoantibodies when B/W lupus mice were immunized with methylated BSA-DNA complex (65).…”
Section: Introductionmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was performed to detect antibodies to nucleosomes, H1, dsDNA, DNase I, type IV collagen, heparan sulfate, and ␣-actinin, as described previously (27)(28)(29)(30). Essentially, microtiter plates (MaxiSorp; Nunc, Copenhagen, Denmark) were coated with nucleosomes (10 g/ml as DNA), dsDNA (10 g/ml), H1 (2 g/ml), heparan sulfate (10 g/ml), ␣-actinin (5 g/ml), DNase I (5 g/ml), and type IV collagen (5 g/ml).…”
Section: Methodsmentioning
confidence: 99%